Herb Formula (GCis) Prevents Pulmonary Infection Secondary to Intracerebral Hemorrhage by Enhancing Peripheral Immunity and Intestinal Mucosal Immune Barrier - Miao, Yulu; Wang, Bin; Hu, Jing; Zhang, Hanyu; Li, Xiaojin; Huang, Yingying; Zhuang, Pengwei; Zhang, Yanjun (Frontiers in Pharmacology, 2022)
Lung infection is a common complication induced by stroke and seriously affects the prognosis and life quality of patients. However, effective therapeutic strategies are still lacking. In the present study herb formula GCis was confirmed to prevent pulmonary infection induced by intracerebral hemorrhage(ICH). The animal model of lung infection induced by ICH, GCis (Ginseng Radix et Rhizoma, Aconiti Lateralis Radix Praeparata, and Cistanches Herba) was oral administrated every day for 7days. Lung microbial biomass and pathological results showed that GCis formula pretreatment significantly reduced lung bacterial biomass and alleviated pathological abnormalities. These results indicated that GCis formula has a clear pharmacological effect on preventing lung infection induced by ICH. Immunosuppression induced by ICH are seemed the main mechanisms of lung infection, our results showed that the spleen and thymus indexes, WBC and LY% contents were significantly increased in GCis formula group. And bone marrow cells were further analyzed by transcriptome sequencing, GO and KEGG enrichment analysis results showed that immune function was the main pathways enriched by differential genes after GCis formula intervention. And more importantly our results showed tha GCis pretreatment had no significant effect on the mRNA expression of IL-1β, IL-6 and TNF-α in the brain. These results indicated that GCis formula can enhanced immunity after ICH. Considering the origin of the source of infection, intestinal barrier function was further investigated in the present study, our results showed that the mRNA expressions of intestinal ZO-1, SIgA and MUC2 were significantly increased and the villi structure was intact, inflammatory cell infiltration was reduced, and goblet cell number was increased after GCis formula treatment. These results suggest that GCis formula can enhance intestinal mucosal immune barrier. Taken together our present study provide a herb formula (GCis) which could enhance peripheral immunity and intestinal mucosal immune barrier to prevent pulmonary infection induced by ICH, it would be beneficial to the prevention of clinical severe infections.